One-Pot Synthesis of 2-Arylindole Derivatives under Transition-Metal-Free Conditions - Kraikruan, Panitan; Rakchaya, Intouch; Sang-aroon, Pattarapon; Chuanopparat, Nutthawat; Ngernmeesri, Paiboon (Synlett, 2022)
A new and simple method for preparing 2-arylindole derivatives under transition-metal-free conditions has been developed. When N-(2-methyl-3-nitrophenyl)acetamide was treated with 2-fluorobenzaldehydes in the presence of Cs2CO3 in DMF at 60 °C, the desired indoles were typically obtained in moderate to good yields (up to 83%). When other aniline substrates were employed, only a Knoevenagel condensation occurred, giving the corresponding diarylethenes in moderate to excellent yields.
Keywords: indoles; one-pot synthesis; transition-metal-free synthesis; cascade reaction; Knoevenagel condensation